Improving Student Learning Outcomes of Islamic Education Materials with a Collaboration Model at SD Negeri 100313 Tabusira - Rayani , Adeka; Hidayah, Nurul; Hikmah, Nurul (Program Studi Pendidikan Profesi Guru Fakultas Tarbiyah dan Keguruan UIN Ar-Raniry Banda Aceh, 2024)
: This research aims to improve student learning outcomes in Islamic religious education learning by using a collaborative model. This research is a classroom action research that uses four steps, namely planning, action, observation and reflection. The subject of this research is elementary school students. The data of this study was obtained by test and observation techniques. Tests are used to measure learning outcomes and observations are used to analyze the learning activities of teachers and students. The data analysis technique used in this study is descriptive statistics by comparing the results obtained with research success indicators. The results of the study show that the collaboration model can improve student learning outcomes in Islamic religious education learning. This can be seen from the increase in the percentage of student learning completeness in each cycle with details of 46.19% in the pre-cycle, 75.37% in the first cycle and 89.92% in the second cycle. Thus, the use of the collaboration model can be used as an alternative to improve student learning outcomes in Islamic religious education learning.